Why are firms that export cleaner? International trade, abatement and environmental emissions - Forslid, Rikard; Okubo, Toshihiro; Ulltveit-Moe, Karen Helene (Journal of environmental economics and management, 2018)
This paper proposes a detailed mechanism for why exporting firms may have a lower emission intensity when emissions are subject to an environmental tax. This mechanism of our model is supported by Swedish firm-level data. Our mechanism runs through firms' endogenous investments in abatement. Firms' abatement investments depend on their production volumes, since a larger scale allows them to spread the fixed costs of abatement investment across more units. Production volumes increase in firm productivity and, as a consequence, firms' emission intensity is negatively related to firm productivity. Exporting also leads to higher production volumes and thereby to a lower emission intensity. Thus, trade has an effect on emissions independently of firm productivity. Trade therefore leads to higher but cleaner production. The overall effect of trade on emissions is neutral in our model. Trade liberalization does not affect aggregate emissions in our benchmark case of symmetric countries.